Addition of Industrial Hemp (Cannabis sativa L.) Dry Inflorescence in Beer Production - Kristina Habschied; Stela Jokić; Krunoslav Aladić; Ivana Šplajt; Vinko Krstanović; Krešimir Mastanjević (Applied Sciences)
Recent research has increasingly focused on the benefits of various plants, including hemp, which has gained prominence for its medical and industrial applications. The incorporation of industrial hemp in beer brewing has further popularized this age-old beverage. In several countries, the cultivation of industrial hemp containing a maximum of 0.2% THC (Δ9-tetrahydrocannabinol) has been legalized, leading to a growing recognition of the plant’s potential and its derived products. The objective of this study was to produce beer infused with dried industrial hemp inflorescences. Additionally, a sensory analysis was conducted with panelists to evaluate the drinkability of the produced beer, revealing that both beer variants with added hemp inflorescence received higher scores. The addition of hemp inflorescence during boiling resulted with a higher specific gravity (1.01071 mg/L) in regard to control beer (1.01015 mg/L) and beer subjected to dry hemping (1.01018 mg/L). Generally, a significant difference for most physical–chemical parameters was noted in the sample boiled with hemp inflorescence, while the control sample and dry-hemped sample showed no statistically significant difference. The only physical–chemical property that showed no difference between all samples, including control, was bitterness, which exhibited no change in relation to the mode of hemp inflorescence addition.